2005
DOI: 10.1038/sj.bmt.1704821
|View full text |Cite
|
Sign up to set email alerts
|

Early vancomycin-resistant enterococcus (VRE) bacteremia after allogeneic bone marrow transplantation is associated with a rapidly deteriorating clinical course

Abstract: Summary:Vancomycin-resistant enterococcal (VRE) infection is a growing threat. We studied the incidence, risk factors, and clinical course of early-onset VRE bacteremia in allogeneic hematopoietic stem cell transplant recipients. We carried out a chart review of 281 allogeneic hematopoietic stem cell transplant recipients from 1997-2003, including preparative regimen, diagnosis, status of disease, graftversus-host disease prophylaxis, antimicrobial therapy, and survival. VRE bacteremia developed in 12/281 (4.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
60
2
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 14 publications
5
60
2
1
Order By: Relevance
“…Avery et al 22 described the outcomes of 12 allogeneic transplant recipients who developed VRE BSI. Ten of 12 patients experienced VRE BSI during the neutropenic period (median 15 days post transplant, range [8][9][10][11][12][13][14][15][16][17][18][19][20][21], and mainly this occurred in patients with refractory or relapsed disease at the time of transplantation (70%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Avery et al 22 described the outcomes of 12 allogeneic transplant recipients who developed VRE BSI. Ten of 12 patients experienced VRE BSI during the neutropenic period (median 15 days post transplant, range [8][9][10][11][12][13][14][15][16][17][18][19][20][21], and mainly this occurred in patients with refractory or relapsed disease at the time of transplantation (70%).…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17][18][19][20][21] Although some studies have indicated VRE infections are associated with worse outcomes in immunocompromised patients, 19,20 data on VRE infections in patients with hematologic malignancies and HSCT recipients are limited. 21,22 Therefore we conducted a retrospective cohort study to determine the patient characteristics associated with VRE BSI and risk factors for death in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 These infections tend to occur early in the post-transplant period, typically before engraftment. 2 Data on the clinical course of these infections has been conflicting with mortality rates attributed to VRE ranging from B10 10 to 100%. 2 A recent meta-analysis clearly documented that VRE, particularly in immunosuppressed patients, was independently associated with increased mortality among patients with enterococcal bloodstream infections.…”
mentioning
confidence: 99%
“…2 Data on the clinical course of these infections has been conflicting with mortality rates attributed to VRE ranging from B10 10 to 100%. 2 A recent meta-analysis clearly documented that VRE, particularly in immunosuppressed patients, was independently associated with increased mortality among patients with enterococcal bloodstream infections. 11,12 Also problematic is the lack of proven, safe and effective regimens in this population to treat VRE infections, which may contribute to a delay in the initiation of appropriate therapy.…”
mentioning
confidence: 99%
See 1 more Smart Citation